In vitro gas production, rumen parameters and nutrients degradability of diets based on Cenchrus ciliaris grass-shrubs and tree leaves in sheep and goats - SINGH, SULTAN; KUNDU, S S; KARNANI, L K (The Indian Journal of Animal Sciences, 2011)
Twenty dietary combination of Cenchrus ciliaris-CC grass with shrubs (Dichrostachys cineria-DC Securengia virosa-SV; Zizyphus xylophyrus-ZX, Helictris isora-HI and Acacia catechu-AC) and tree leaves (Hardwickia binata-HB, Albizia lebbek-AL, Grewia optiva-GO, Anogessus pendullaAP and Leucaena leucocephala-LL) in 50:50 and 75:25 ratios were evaluated for in vitro gas production, nutrients degradation and metabolites production in sheep and goat inoculums. Â